Factors influencing muslims’ purchase intention of halal-certified over-the-counter (OTC) medicines in Bekasi, Indonesia - Fatmi, Fitry Oktavia; Ahmad, Anis Najiha; Muflih, Betania Kartika (Universitas Airlangga, 2024)
Self-medication in Indonesia has recently increased; consumers can easily purchase non-prescription medicines, many people use over-the-counter (OTC) medicines as an alternative for self-medication. In this study, the researchers have chosen to address the gap in the literature pertaining to purchase intention on halal pharmaceuticals, whereas, the focus is on purchase intention of halal certified OTC medicines. This study was conducted in Bekasi, Indonesia. 325 Muslim consumers in Bekasi, Indonesia, participated in this study. The information was gathered using questionnaires with convenient sampling techniques. Through utilizing the theory of consumption value, which consists of the factors of functional value (price), functional value (quality), social value (pharmacist advice), emotional value (halal logo), conditional value, and epistemic value of respondents' intentions to purchase halal-certified OTC medicines. The findings of this study, three factors: functional value (quality), emotional value, and epistemic value, have a significant relationship with the purchase intention of halal-certified OTC medicines in Bekasi, Indonesia.